High-efficiency preparation of poly(2-methacryloyloxyethyl phosphorylcholine) grafting layer on poly(ether ether ketone) by photoinduced and self-initiated graft polymerization in an aqueous solution in the presence of inorganic salt additives. (August 2016) - Shiojima, Taro; Inoue, Yuuki; Kyomoto, Masayuki; Ishihara, Kazuhiko
Graphical abstract: Abstract: A highly efficient methodology for preparing a poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC) layer on the surface of poly(ether ether ketone) (PEEK) was examined by photoinduced and self-initiated graft polymerization. To enhance the polymerization rate, we demonstrated the effects of inorganic salt additives in the feed monomer solution on thickness of grafted PMPC layer. Photoinduced polymerization occurred and the PMPC graft layer was successfully formed on the PEEK surface, regardless of inorganic salt additives. Moreover, it was clearly observed that the addition of inorganic salt enhanced the grafting thickness of PMPC layer on the surface even when the photoirradiation time was shortened. The addition of inorganic salt additives in the feed monomer solution enhanced the polymerization rate of MPC and resulted in thicker PMPC layers. In particular, we evaluated the effect of NaCl concentration and how this affected the polymerization rate and layer thickness. We considered that this phenomenon was due to the hydration of ions in the feed monomer solution and subsequent apparent increase in the MPC concentration. A PMPC layer with over 100-nm-thick, which was prepared by 5-min photoirradiation in 2.5 mol/L inorganic salt aqueous solution, showed good wettability and protein adsorption resistance compared to that of untreated PEEK. Hence, we concluded that the addition of NaCl into the MPC feed solution would be a convenient and efficient method for preparing a graft layer on PEEK. Statement of Significance: Photoinduced and self-initiated graft polymerization on the PEEK surface is one of the several methodologies available for functionalization. However, in comparison with free-radical polymerization, the efficiency of polymerization at the solid-liquid interface is limited. Enhancement of the polymerization rate for grafting could solve the problem. In this study, we observed the acceleration of the polymerization rate of MPC in an aqueous solution by the addition of inorganic salt. The salt itself did not show any adverse effects on the radical polymerization; however, the apparent concentration of the monomer in feed may be increased due to the hydration of ions attributed to salt additives. We could obtain PMPC-grafted PEEK with sufficient PMPC thickness to obtain good functionality with only 5-min photoirradiation by using 2.5 mol/L NaCl in the feed solution.